Soybean dependence on biotic pollination decreases with latitude - Leme Da Cunha, Nicolay (2023)
Identifying large-scale patterns of variation in pollinator dependence (PD) in crops is important from both basic and applied perspectives. Evidence from wild plants indicates that this variation can be structured latitudinally. Individuals from populations at high latitudes may be more selfed and less dependent on pollinators due to higher environmental instability and overall lower temperatures, environmental conditions that may affect pollinator availability. However, whether this pattern is similarly present in crops remains unknown. Soybean (Glycine max), one of the most important crops globally, is partially self-pollinated and autogamous, exhibiting large variation in the extent of PD (from a 0 to ∼50% decrease in yield in the absence of animal pollination). We examined latitudinal variation in soybean's PD using data from 28 independent studies distributed along a wide latitudinal gradient (4–43 degrees). We estimated PD by comparing yields between open-pollinated and pollinator-excluded plants. In the absence of pollinators, soybean yield was found to decrease by an average of ∼30%. However, PD decreases abruptly at high latitudes, suggesting a relative increase in autogamous seed production. Pollinator supplementation does not seem to increase seed production at any latitude. We propose that latitudinal variation in PD in soybean may be driven by temperature and photoperiod affecting the expression of cleistogamy and androsterility. Therefore, an adaptive mating response to an unpredictable pollinator environment apparently common in wild plants can also be imprinted in highly domesticated and genetically-modified crops.